Influence of Media Globalization on Denigration of National Values in African Children - Ehondor, Beryl Annette (Journal of Marketing Development and Competitiveness, 2020)
Media globalization has eased the availability of entertainment for African Children, particularly via cable-TV. Considering the power of media as socialization_agent, this research appraised proliferation of children shows on DsTv/GoTv via the lens of African cultural particulars, particularly respect for elders and authoritative parenting. Using media_content_analysis methodology and discourse_analysis, findings link global_media influence as the mechanism for the denigration of African values in children, with Social_cognitive_theory framing the implications. Recommendations are stronger national broadcast regulations for reinforcement of family values via television to preserve the identity of society, providing local content for global export and contributing to glocal media content.